Advances in rugby coaching an holistic approach - Light, Richard 1951-; Evans, John R.; Harvey, Stephen; Hassanin, Remy (Routledge, Taylor & Francis Group, 2015)
"Contemporary sports coaching studies have moved beyond simple biophysical approaches to more complex understandings of coaching as a set of social relationships and processes. This is the first book to examine what that means in the context of one major international sport, rugby union. Drawing on cutting-edge empirical research in the five most powerful rugby-playing nations, as well as developments in pedagogical and social theory, the book argues for an holistic approach to coaching, coach development and player and team performance, helping to close the gap between coaching theory and applied practice. With player-centered approaches to coaching, such as Game Sense and Teaching Games for Understanding, at the heart of the book, it covers key contemporary topics in coach education such as: Long term coach development Experience and culture in coaching practice Positive coaching for youth rugby Improving decision-making ability Collaborative action research in rugby coaching Informed by work with elite-level rugby coaches, and examining coaching practice in both the full and sevens versions of the game, this book encourages the reader to think critically about their own coaching practice and to consider innovative new approaches to player and coach development. It is essential reading for all students of sports coaching with an interest in rugby, and for any coach, manager or administrator looking to develop better programmes in coach education"--